Pacific oyster polyamine oxidase: a protein missing link in invertebrate evolution - Cervelli, Manuela; Polticelli, Fabio; Angelucci, Emanuela; Di Muzio, Elena; Mariottini, Paolo; STANO, Pasquale (Amino Acids, 2015)
Polyamine oxidases catalyse the oxidation of polyamines and acetylpolyamines and are responsible for the polyamine interconversion metabolism in animal cells. Polyamine oxidases from yeast can oxidize spermine, N(1)-acetylspermine, and N(1)-acetylspermidine, while in vertebrates two different enzymes, namely spermine oxidase and acetylpolyamine oxidase, specifically catalyse the oxidation of spermine, and N(1)-acetylspermine/N(1)-acetylspermidine, respectively. In this work we proved that the specialized vertebrate spermine and acetylpolyamine oxidases have arisen from an ancestor invertebrate polyamine oxidase with lower specificity for polyamine substrates, as demonstrated by the enzymatic activity of the mollusc polyamine oxidase characterized here. This is the first report of an invertebrate polyamine oxidase, the Pacific oyster Crassostrea gigas (CgiPAO), overexpressed as a recombinant protein. This enzyme was biochemically characterized and demonstrated to be able to oxidase both N(1)-acetylspermine and spermine, albeit with different efficiency. Circular dichroism analysis gave an estimation of the secondary structure content and modelling of the three-dimensional structure of this protein and docking studies highlighted active site features. The availability of this pluripotent enzyme can have applications in crystallographic studies and pharmaceutical biotechnologies, including anticancer therapy as a source of hydrogen peroxide able to induce cancer cell death.